2016
DOI: 10.1097/md.0000000000003013
|View full text |Cite
|
Sign up to set email alerts
|

Risk Factors for Development and Progression of Chronic Kidney Disease

Abstract: Supplemental Digital Content is available in the text

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
93
2
6

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 133 publications
(108 citation statements)
references
References 42 publications
7
93
2
6
Order By: Relevance
“…The disease accounted for 53.61% of the cases in the present study, which is similar to previous studies that reported 55% (3,4). Hypertension is a risk factor of CKD and also a common complication of CKD (22,23). With the progression of CKD, 80-85% patients have elevated blood pressure.…”
Section: % CI ------------------------------Variablesupporting
confidence: 80%
“…The disease accounted for 53.61% of the cases in the present study, which is similar to previous studies that reported 55% (3,4). Hypertension is a risk factor of CKD and also a common complication of CKD (22,23). With the progression of CKD, 80-85% patients have elevated blood pressure.…”
Section: % CI ------------------------------Variablesupporting
confidence: 80%
“…Many studies suggest that male sex is associated with worse renal outcomes [21-24], consistent with the present study (Table 2). Sex differences exist in the pathogenesis and clinical prognosis of CKD [25], and female sex seems to be renoprotective for the development and progression of CKD.…”
Section: Discussionsupporting
confidence: 82%
“…The results of studies on elderly status as a prognostic factor for renal prognosis have been inconsistent [21]. In the present study, although elderly status was associated with slightly better renal outcomes in the total cohort (Table 2), the prognostic characteristics of elderly patients in the Kaplan-Meier analyses differed according to the BMI-based cross-classified subcohort (Fig.…”
Section: Discussioncontrasting
confidence: 46%
See 2 more Smart Citations